Placental features of mirror syndrome: a case report. (18th April 2012) - Graham, N; McVey, R; Bullen, P; Heazell, A
Abstract : Mirror syndrome, is a rare condition characterised by the combination of fetal hydrops and maternal oedema. Mirror syndrome is rare, consequently the pathogenesis and pathophysiology is unknown. It is associated with increased fetal mortality and maternal morbidity. In this case, a 25 year old Gravida 2Para 1 was referred to our unit with fetal supraventricular tachycardia diagnosed at 27 weeks gestation, when digoxin was commenced. At 28+2 weeks ultrasound revealed polyhydramnios and ascities and fetal hydrops. The patient was admitted at 29 weeks gestation with epigastric pain, vomiting and severe oedema. She had raised urea and creatinine, liver function, and hypoalbuminaemia and coagulopathy. She was normotensive and with proteinuria. While the maternal condition was being stabilised, fetal death in-utero was confirmed. The patient became anuric with severe renal and hepatic impairment. Labour was induced and progressed quickly to a NVD. The patient made a slow recovery complicated by a pancreatic cyst. By 3 month postnatal all blood results had normalised. Placental histology showed increased intervillous fibrin and focal oedema. Immunostaining showed increased apoptosis, increased syncytial nuclear aggregates, with no alteration in proliferation, vascularity or trophoblast thickness in the villous placenta. Expression of VEGFR1 appeared to be increased in the syncytiotrophoblast. Therefore, there are some similarities in villous trophoblast between mirror syndrome and in pre-eclampsia. This may reflect related pathophysiologies i.e. placental dysfunction releasing vasoactive factors into maternal circulation. However, there are several hypothesises regarding the aetiology of mirror syndrome and further studies on the role of the placenta are needed.